2009
DOI: 10.1038/aps.2009.32
|View full text |Cite
|
Sign up to set email alerts
|

Topotecan inhibits cancer cell migration by down-regulation of chemokine CC motif receptor 7 and matrix metalloproteinases

Abstract: Aim:The aim of this study was to investigate the effect of topotecan (TPT) on cancer cell migration. Methods: Growth inhibition of TPT was analyzed by MTT assay, and cancer cell migration was measured by transwell double chamber assay. To verify the effect of TPT on the chemokine receptors CXCR4 and CCR7, quantitative PCR, semiquantitative PCR and Western blot analysis were performed. The secretion of MMP-2 and MMP-9 was detected by enzymelinked immunosorbent assay (ELISA) and gelatin zymography. To evaluate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…These results suggest that ethoxidine is able to differentially regulate events leading to angiogenesis. Similar results have been reported with topotecan, which mediates activation of transcription factors that regulate MMP2 expression both in tumor cells (29) and in endothelial cells (30) suggesting that it affects both tumor cells and endothelial cells for its therapeutic property when it is used at high concentration (10 À7 to 10 À6 M). Also, it is clear from the present study that ethoxidine at a concentration at which it had no reported effect on tumor cells (i.e.…”
Section: Discussionsupporting
confidence: 83%
“…These results suggest that ethoxidine is able to differentially regulate events leading to angiogenesis. Similar results have been reported with topotecan, which mediates activation of transcription factors that regulate MMP2 expression both in tumor cells (29) and in endothelial cells (30) suggesting that it affects both tumor cells and endothelial cells for its therapeutic property when it is used at high concentration (10 À7 to 10 À6 M). Also, it is clear from the present study that ethoxidine at a concentration at which it had no reported effect on tumor cells (i.e.…”
Section: Discussionsupporting
confidence: 83%
“…MDA-MB-231 cells are known to express CCR7 (23,24) and migrate toward increasing concentration of CCL21 when cultured in 2D and exposed to a CCL21 gradient (25). The system consists of two channels separated by a region containing single cells suspended in a collagen I gel (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, targeted delivery of the gene delivery system expressing CCR7 antagonistic proteins to the tumour site significantly inhibited CCL21/CCR7-mediated tumour cell lymphatic migration by blocking the binding of CCL21 to CCR7 in 4T1 and B16F10 30 . In addition, CCR7 can be downregulated by topotecan, a semi-synthetic analogue of camptothecin, thereby inhibiting metastasis in breast cancer 49 . In this study, PTX treatment could delay tumour growth but increase the risk of tumour metastasis, but inhibition of CCR7 could decrease the PTX-induced migration of B16F10 cells.…”
Section: Discussionmentioning
confidence: 99%